De novo morphogenesis in L‐forms via geometric control of cell growth. Issue 5 (23rd July 2014) - Billings, Gabriel; Ouzounov, Nikolay; Ursell, Tristan; Desmarais, Samantha M.; Shaevitz, Joshua; Gitai, Zemer; Huang, Kerwyn Casey
Summary In virtually all bacteria, the cell wall is crucial for mechanical integrity and for determining cell shape. Escherichia coli's rod‐like shape is maintained via the spatiotemporal patterning of cell‐wall synthesis by the actin homologue MreB. Here, we transiently inhibited cell‐wall synthesis in E. coli to generate cell‐wall‐deficient, spherical L‐forms, and found that they robustly reverted to a rod‐like shape within several generations after inhibition cessation. The chemical composition of the cell wall remained essentially unchanged during this process, as indicated by liquid chromatography. Throughout reversion, MreB localized to inwardly curved regions of the cell, and fluorescent cell wall labelling revealed that MreB targets synthesis to those regions. When exposed to the MreB inhibitor A22, reverting cells regrew a cell wall but failed to recover a rod‐like shape. Our results suggest that MreB provides the geometric measure that allows E. coli to actively establish and regulate its morphology.